A miniaturized 28 GHz 4‐bit phase shifter in 65 nm LP CMOS for multi‐channel 5‐G radios. Issue 2 (7th December 2018) - Lee, Junghwan; Seo, Munkyo
Absract: A 65 nm LP CMOS 4‐bit phase shifter for 28 GHz 5G applications is presented. Sharing inductor footprints and using a switched inductor allow ~50% of layout size reduction, compared to conventional design. On‐wafer testing shows that the fabricated phase shifter exhibits 14.3 dB average insertion loss over the 27.5–28.35 GHz band. Measured input and output return losses are >7.2 dB. Measured RMS phase and gain error are 9.4° and 2.7 dB at 28 GHz, respectively. Measured input P1dB is >11 dBm. The chip area excluding pads is 0.067 mm 2, × 2 more compact than previous Ka‐band phase shifters, to the best of authors' knowledge. The presented phase shifter allows low‐cost IC implementation of multi‐channel 5G transceivers.